Development of a monitoring instrument to assess the performance of the Swiss primary care system - Sonja T. Ebert; Valérie Pittet; Jacques Cornuz; Nicolas Senn (BMC, 2017)
Abstract Background The Swiss health system is customer-driven with fee-for-service paiement scheme and universal coverage. It is highly performing but expensive and health information systems are scarcely implemented. The Swiss Primary Care Active Monitoring (SPAM) program aims to develop an instrument able to describe the performance and effectiveness of the Swiss PC system. Methods Based on a Literature review we developed a conceptual framework and selected indicators according to their ability to reflect the Swiss PC system. A two round modified RAND method with 24 inter−/national experts took place to select primary/secondary indicators (validity, clarity, agreement). A limited set of priority indicators was selected (importance, priority) in a third round. Results A conceptual framework covering three domains (structure, process, outcome) subdivided into twelve sections (funding, access, organisation/ workflow of resources, (Para-)Medical training, management of knowledge, clinical−/interpersonal care, health status, satisfaction of PC providers/ consumers, equity) was generated. 365 indicators were pre-selected and 335 were finally retained. 56 were kept as priority indicators.- Among the remaining, 199 were identified as primary and 80 as secondary indicators. All domains and sections are represented. Conclusion The development of the SPAM program allowed the construction of a consensual instrument in a traditionally unregulated health system through a modified RAND method. The selected 56 priority indicators render the SPAM instrument a comprehensive tool supporting a better understanding of the Swiss PC system's performance and effectiveness as well as in identifying potential ways to improve quality of care. Further challenges will be to update indicators regularly and to assess validity and sensitivity-to-change over time.